Humanized Culture Medium for Clinical Expansion of Human Erythroblasts - Migliaccio, Giovanni (Cell Transplant, 2010)
Ex vivo-generated erythroblasts represent alternative transfusion products. However, inclusion of bovine components in media used for their growth precludes clinical use, highlighting the importance of developing culture media based on pharmaceutical grade reagents. In addition, because adult blood generates ex vivo lower numbers of erythroblasts than cord blood, cord blood has been proposed as the source of choice for ex vivo erythroblast production. To clarify the potential of adult blood to generate erythroblasts ex vivo, experiments were designed to identify growth factors [stem cell factor (SCF), interleukin-3 (IL-3), erythropoietin (EPO), and/or thrombopoietin (TPO)] and the optimal concentration and addition schedule of hormones (dexamethasone and estradiol) sustaining maximal erythroid amplification from adult blood mononuclear cells (MNC) using media with serum previously defined as human erythroid massive amplification culture (HEMA(ser)). Adult MNC stimulated with SCF and IL-3 in combination with EPO generated a 6–12-fold increase in erythroid cells while TPO was ineffective. Dexamethasone and estradiol (both at 10(−6) M) exerted partially overlapping but nonredundant functions. Dexamethasone was indispensable in the first 10 days of culture while estradiol was required from day 10 on. The growth factor and hormone combinations identified in HEMA(ser) were then used to formulate a media composed of dialyzed pharmaceutical grade human albumin, human albumin-lipid liposomes, and iron-saturated recombinant human tranferrin (HEMA(def)). HEMA(def) sustained erythroid amplification as efficiently as HEMA(ser) for cord blood MNC and 10-fold higher than HEMA(ser) for adult blood MNC. In fact, the numbers of erythroblasts generated in HEMA(def) by adult MNC were similar to those generated by cord blood MNC. In conclusion, this study identifies growth factors, hormone combinations, and human protein-based media that allow similar levels of ex vivo erythroid expansion from adult and cord blood MNC, paving the way to evaluate adult blood as a source of ex vivo-expanded erythroblasts for transfusion.